Cyberbullying in high school and university: Description, comparison, and associations between behaviors in victims and aggressors - Mendoza González, Brenda (2025)
Introduction: Experiences of cyberbullying can have lasting effects on victims' self-esteem, social relationships, and overall well-being. Objective: This study aims to determine the association between cyberbullying behaviors, both as victims and aggressors, in high school and university students, identifying differences and similarities between the two educational contexts. Methods: We conducted a cross-sectional study with 402 participants (203 women and 199 men), including 200 high school students and 202 university students. Both institutions were public and located in urban areas of the State of Mexico's capital. Cyberbullying was assessed using the Cyberbullying Questionnaire, which evaluates multiple forms of cyberbullying. Results: University students were more likely than high school students to engage in cyberbullying as aggressors, with a large effect size. Among high school students, a strong association was observed between being victims of cyberbullying through the spread of secrets and the repeated receipt of disturbing messages (r = .659). In university students, significant co-occurrence of behaviors was identified within the aggressor subscale, revealing associations between grooming, sexting, denigration, exclusion, and happy slapping. Conclusions: These findings underscore the importance of implementing intervention programs in upper secondary and higher education settings, where action protocols are typically less established compared to basic education levels.